Teachers’ Challenges in Optimizing Students’ Speaking Skills by Using Flipped Classroom - Sutrisno, Trisno; Rohayati, Dedeh; Irianti, Leni (Universitas Galuh, 2024)
The majority of people are concentrating on using technology for many things, including communication. Technology significantly affects learning outcomes in educational environments. It depends on the teacher's technological know-how and competence. With technology, it might be simpler to decide whether a teacher should join the class in person or virtually. Delivering lectures with a creative and engaging design is a wonderful way to get students excited. The flipped classroom is a new paradigm in learning that has been utilized by teachers. In this approach, the teacher can present the lectures online and then discuss them offline during the following meeting. Since the pandemic had nearly coming to an end and teachers should be able to switch between online classes and offline classes, flipped classrooms have grown in popularity. This research is a narrative study that aims to identify the teachers' challenges in optimizing students' speaking skills by using flipped classroom. Speaking has a crucial part in determining a student's success in language learning. In order to confirm the beneficial effects of flipped classroom in speaking classes, the present research aims to elaborate teachers' perceptions in improving students' speaking skills through flipped classroom. The participants in this study were 4 English teachers from two senior high schools in East Priangan, West Java. The research employed a qualitative approach to gather data, by using a diary and an interview. The diary includes a few questions on their experiences with the flipped classroom implementation process, and the interview covers the challenges, strategies, and perspectives faced by doing so in order to improve students' speaking abilities. The results of this study proved that employing flipped classrooms made teachers feel more supported and students' speaking abilities increased. Additionally, flipped classrooms have a beneficial effect on learning activity because they may foster active learning.